Major Pettigrew's last stand a novel - Simonson, Helen (Random House Trade Paperbacks, 2010)
Major Ernest Pettigrew (retired) leads a quiet life in the village of St. Mary, England, until his brother's death sparks an unexpected friendship with Mrs. Jasmina Ali, the Pakistani shopkeeper from the village. Drawn together by their shared love of literature and the loss of their respective spouses, the Major and Mrs. Ali soon find their friendship blossoming into something more. But will their relationship survive in a society that considers Ali a foreigner?
Keywords: Country life -- England -- Fiction; Retirees -- Fiction; Widowers -- Fiction; Widows -- Fiction; Pakistanis -- England -- Fiction; Interracial friendship -- Fiction; Fiktionale Darstellung